2019
DOI: 10.3390/data4010033
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis of the Marine Bacterium Labrenzia sp. Strain 011, a Potential Protective Agent of Mollusks

Abstract: The marine bacterium Labrenzia sp. strain 011 was isolated from the coastal sediment of Kronsgaard, Germany. The Labrenzia species are suggested to be protective agents of mollusks. Labrenzia sp. strain 011 produces specialized metabolites, which showed activity against a range of microorganisms, thereunder strong inhibitory effects against Pseudoroseovarius crassostreae DSM 16,950 (genus Roseovarius), the causative agent of oyster disease. The genome of Labrenzia sp. strain 011 was sequenced and assembled int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In order to elucidate the putative biosynthesis of compounds 1 and 2 , the genome of Labrenzia sp. 011 has recently been sequenced (accession number: QCYM00000000) [ 35 ]. The resulting genome was compared with further available genome sequences of the genus Labrenzia .…”
Section: Resultsmentioning
confidence: 99%
“…In order to elucidate the putative biosynthesis of compounds 1 and 2 , the genome of Labrenzia sp. 011 has recently been sequenced (accession number: QCYM00000000) [ 35 ]. The resulting genome was compared with further available genome sequences of the genus Labrenzia .…”
Section: Resultsmentioning
confidence: 99%
“…42,43 Bacteria of the genus Labrenzia are known as surface colonizers in marine environments and are suggested to act as protective symbionts of oysters. 44 In a recent study, Labrenzia sp. strain 011, isolated from Baltic Sea coastal sediment was found to produce two medium-chain fatty acids containing a cyclopropane moiety: cis-4-(2-hexylcyclopropyl)-butanoic acid (1) and cis-2-(2-hexylcyclopropyl)-acetic acid (2).…”
Section: Medium-chain Cyclopropane-containing Fatty Acidsmentioning
confidence: 97%
“…strain 011, isolated from Baltic Sea coastal sediment was found to produce two medium-chain fatty acids containing a cyclopropane moiety: cis-4-(2-hexylcyclopropyl)-butanoic acid (1) and cis-2-(2-hexylcyclopropyl)-acetic acid (2). 44,45 Both compounds were isolated using absorber resin Sepabeads from 20 L culture and the structures were established by NMR analyses. Activity studies revealed their inhibition activity against a range of bacteria and fungi, including a causative agent of Roseovarius oyster disease (ROD), Pseudoroseovarius crassostreae DSM 16950.…”
Section: Medium-chain Cyclopropane-containing Fatty Acidsmentioning
confidence: 99%